Dinamika Politik Partai Lokal dan Nasional Pada Pemilukada di Aceh, Tahun 2017 - Muhammad Nur; Usman Usman; Irwan Safwadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
This study aims to find out the political dynamics of regional and national parties in Acehs’ regioal election 2017. This study is also aimed to investigate the factors that influence the political dynamics of that particular regional election. The political dynamics in Aceh is very fluctuated. This fluctuation may be caused by the escalation of lobbying done by the political parties that has dominant influence. However, this domination seems to change from time to time particularly in certain districs. In Bireun district for example, the figures from certain national parties had been acknowledged by the local community in the previous regional election in 2017. This change was not only occured in the executive level but also in the composition of legislative members in the regional election as seen in 2014 elections’. This study used the qualitative descriptive method. The data was collected mainly from words, sentences or images that have insight meaning and trigger more tangible understanding than numbers or frequencies. The data was gathered from interview and observation in Banda Aceh. As for qualitative research, the data collection was carried out in the natural setting. The primary data source and data collection technique were more focus on the observation, in-depth interview and also documentation. The result showed that the dynamics of political development between regional and national parties were very dynamic. This dynamic was influenced by the fundamental aspect in politics, that is the interest of the party. The study suggested that the interest between regional and national parties at the district and provincial level have different degree of interest. However, in order to get the seat in the national parliament, these parties might be enggage in a political compromise. On the other hand, the political dynamics between regional and national parties lies in the party ideology itself.